Learning Experiences of Highly Able Learners With ASD: Using a Success Case Method. (September 2019) - Wu, I-Chen; Lo, C. Owen; Tsai, Kuei-Fang
Empirical studies investigating twice-exceptional students' learning experiences and intricate needs remain scarce to date. Even though highly able learners with autism spectrum disorder (ASDs) demonstrate potential for high achievement and/or creative productivity, they also face potential psychosocial distresses such as anxiety disorders and poor self-concept. This study aimed to explore positive educational opportunities for highly able learners diagnosed with ASD. Using a success case method, the researchers invited two fifth-grade highly able learners with ASD to participate in this study. Data collection included interviews, observations, questionnaires, and supplementary artifacts. Adopting a general inductive analysis approach and a Glaserian coding paradigm, the researchers identified a core category, supportive school context (SSC), along with three subcategories: (a) curriculum flexibility, (b) strength-based approaches, and (c) safe environment. The findings could provide effective pedagogical strategies for teachers, school administrators, and parents. Furthermore, we rendered several suggestions for future research.